Islamic Banking Selection Criteria: Case in Indonesia Using Analytic Network Process - Aam Slamet Rusydiana; Fatin Fadhilah Hasib (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
The Islamic banking industry is currently one of the main indicators of the development of Islamic economics in Indonesia. In Islamic banking issue, one of the important issues is related to people's preferences and behavior towards Islamic banks. The study of the criteria for selecting a bank has been the concern of many bank marketing researchers. Compared to conventional, such studies are relatively minimal, especially in Indonesia. This study tries to analyze the preferences and behavior of criteria for selection of Islamic banks in Indonesia through the Analytical Network Process (ANP) approach.The results conclude that the most priority criteria that influence the selection of Islamic banks in Indonesia are service factors and religiosity factors or the suitability of banks with sharia principles. Therefore, Islamic banks need to constantly improve the quality of services both services and products so that they can compete with conventional banks.Industri perbankan syariah saat ini merupakan salah satu indikator utama perkembangan ekonomi Islam di Indonesia. Dalam masalah perbankan syariah, salah satu masalah penting adalah terkait dengan preferensi dan perilaku pemilihan masyarakat terhadap bank syariah. Studi tentang kriteria pemilihan bank syariah telah menjadi perhatian banyak peneliti. Studi tersebut relatif minimal jika dibandingkan dengan bank konvensional, terutama di Indonesia. Penelitian ini mencoba menganalisis preferensi dan perilaku pemilihan kriteria bank syariah di Indonesia melalui pendekatan Analytical Network Process (ANP). Hasilnya menyimpulkan bahwa kriteria yang paling prioritas yang mempengaruhi nasabah dalam memilih bank syariah di Indonesia adalah faktor layanan dan faktor religiusitas atau kesesuaian bank dengan prinsip syariah. Oleh karena itu, bank syariah perlu terus meningkatkan kualitas layanan baik produk maupun jasa sehingga mereka dapat bersaing dengan bank konvensional.